(untitled) (Veterinary Science, 2017)
This approach is based on the following theoretical and methodological assumptions: the classroom should be an environment for exchange between experiential and academic culture. The firstone will be point of departure where the new contents activate habitual schemas of acting and thinking. Thus we can sate that the acquisition of the academic culture should take place trough a process of reconstruction rather than imposition Furthermore, its important to generate an at mosphere of meaningful learning to foster a reflective and critical attitude on the part of student, who should be able to establish a relationship between pre-existing cognitive structures and the knowledge. This approach will result in a total comprehension of the new theoretical and practical propositions. This approach will be developed in the Medical Pathology Course of the Internal Medicine Department. This is an annual course dictated to sixty students in thefourth year ofVeterinary Medicine. The activities are based on a problem situation, where bibliographic resources will be required. The topic "Downer Cow Syndrome" is broad, considering that it can be caused by different pathologies. For this reason, it is important to intercalate practice and theory, where the student should use the knowledge he has acquired in other subjects to find out the pathologic agent that caused the animals decubitus.